Development and Psychometric Evaluation of the Gender Identity Scale for Transgender Women in China - Han, Meng; Pan, Bailin; Wang, Yuanyuan; Wilson, Amanda; Chen, Runsen; Wu, Rengang (Frontiers in Psychology, 2022)
Transgender women are an important subgroup of the transgender umbrella and have their own unique gender identity. This article aimed to understand and measure the latent concept of gender identity among Chinese transgender women from a multi-dimensional perspective. Through a two-phase, iterative scale development process, we developed the Gender Identity Scale for Transgender Women (GIS-TW) in Chinese. Literature reviews, expert consultations, and focus groups constitute phrase 1 of the study, which resulted in the first version of GIS-TW with 30 items. In phrase 2, exploratory factor analysis on a sample of 244 Chinese transgender women revealed a six-factor solution across the 22 items. The Bem Sex Role Inventory was included to test for convergent validity, and the Rosenberg Self-Esteem Scale was used to test discriminant validity. Then we conducted the confirmatory factor analysis with an independent sample of 420 Chinese transgender women, which produced the final version of GIS-TW with 21 items. The internal consistency (Cronbach’s alpha = 0.71–0.87) and test-retest stability (r = 0.73–0.87) of each factor was good. In conclusion, the GIS-TW is a reliable and valid psychometric tool for the assessment of Chinese transgender women’s gender identity. Future application of the scale will help transgender women obtain better gender confirmative interventions.